Treatment outcomes of sinonasal tumours with neuroendocrine features - Valente, Pedro; Farinha, Mónica; Jácome, Manuel; Guimarães, Joana; Monteiro, Eurico (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Sinonasal tumours with neuroendocrine immunophenotype include olfactory neuroblastoma (ONB), sinonasal neuroendocrine carcinoma (SNEC) and sinonasal undifferentiated carcinoma (SNUC). These neoplasms usually present in advanced stages and are associated with poor outcome. This study describes the clinical features of these tumours and analyzes treatment outcomes of patients with these malignancies. Methods: Retrospective chart review of all patients with sinonasal tumours diagnosed from 2009 to 2019, in a tertiary cancer centre. Clinical and histopathological prognostic factors were determined by univariate analysis. Overall survival was estimated using Kaplan-Meier method. Results: A total of 27 patients (77.8% male) with a mean age of 52.0±16.8 years were included in the study. ONB was diagnosed in 9 patients, SNEC in 10 patients and SNUC in 8 patients. TNM stage IV disease was found in 20 patients (74.0%) at presentation. According to staging and treatment results, curative therapy was attempted in 21 patients (77.8%), of whom sixteen (76.2%) received multimodality treatment. Overall mean survival was 49 months and 1-year, 3-years and 5-years overall survival rates were 70.5%, 47.3% and 37.8%, respectively. Patients with SNEC had worse overall survival (p=0.044). Regarding treatment options, patients with SNUC treated with surgery and adjuvant radiation therapy had improved overall survival (p=0.027), as well as patients with SNEC selected for endoscopic resection surgery (p=0.049). Conclusions: Accurate histologic diagnosis, grading, and clinical staging are essential for characterization and treatment selection in this heterogeneous group of sinonasal tumours. Consensus in the management of these tumours is lacking due to their rarity, difficulties in diagnosis and diverse current treatment approaches.